Numerical investigation of installation and environmental parameters on soiling of roof-mounted solar photovoltaic array. Issue 1 (1st January 2019) - Chiteka, Kudzanayi; Sridhara, S. N.; Arora, Rajesh
Abstract: A study of dust deposition on solar photovoltaics as influenced by the installation tilt angle, azimuth angle and the dust particles sizes was carried out. A 3-dimensional Computational Fluid Dynamics (CFD) simulation model was used with the Shear Stress Transport k-ω turbulence model being employed for wind flow analysis and discrete phase model was used for dust motion prediction. Response surface modelling was used to analyse the relationships between the installation parameters, dust particle sizes and dust deposition. The investigation revealed that in a 3-dimensional simulation, the influence of tilt angle is almost similar to the effect of azimuth angle for multi-storey rooftop photovoltaic arrays. Dust particle size of 100 µm had the most deposition resulting in more soiling compared to the 10 µm size dust particles. Soiling of roof-mounted solar PV modules is less on multi-storey building installations compared to ground-mounted solar PV arrays which experienced 13% more deposition. Manipulation of the installation azimuth and tilt angles on roof-mounted installations can be effectively used for soiling minimisation.